Interaksi Hidrokoloid dan Garam Terhadap Karakteristik Organoleptik Salty Cookie Bebas Gluten Substitusi Tepung Sukun dan Tepung Maizena - Hidayah, Isti Nurul; Ferdiansyah, M. Khoiron; Ujianti, Rizky Muliani Dwi (Program Studi Teknologi Pangan, 2021)
Breadfruit flour (Artocarpus communis) is a gluten-free flour which is good to be used as an alternative in making cookies for people with gluten intolerance. The processing of non-gluten cookies has a weakness because there is no function of gluten so that a substitute is needed to improve the properties of cookies with hydrocolloids. Hydrocolloid can form elasticity and compactness well if salt is added. This study aims to determine the interaction of adding hydrocolloid and salt to the sensory properties of gluten-free cookies. The study used a completely randomized design with 2 factorials. The first factor is the type of hydrocolloid (Guar Gum and Xanthan Gum). The second factor is the type of salt (NaCl and CaCl2). The results showed the best treatment on guar gum and NaCl treatment. The addition of hydrocolloid and salt showed (p0,05) and Ho was accepted, so there was no difference in interaction in determining the sensory properties of salty cookies with the parameters of breadfruit aroma, savory taste, salty taste, crunchiness, and brown color.